Status of Prospective Science Teachers’ Critical and Creative Thinking Skills in Energy and Its Integration Topics - Hendratma Gunawan, Kadek Dwi; Liliasari, Liliasari; Kaniawati, Ida; Riandi, Riandi (Jurnal Pendidikan Fisika, 2024)
Developing critical and creative thinking skills is essential for prospective science teachers to address complex scientific problems and design effective integrated science learning. This study aimed to evaluate the critical and creative thinking skills of prospective science teachers, particularly on energy and its integration with other scientific topics. A total of 76 prospective science teachers from a university in East Java, Indonesia, participated in the study. Data were collected using essay tests, observation sheets, and interviews, with critical thinking indicators based on the Ennis framework and creative thinking indicators based on the Guilford framework. The data were analyzed descriptively. The results indicated that students' critical and creative thinking skills were generally in the low category across most indicators. In critical thinking, difficulties were observed in areas such as inference, advanced clarification, and strategy formulation. Similarly, in creative thinking, low scores were evident in fluency, flexibility, originality, and elaboration indicators. These findings highlight the urgent need for instructional innovations and targeted interventions to enhance critical and creative thinking skills among prospective science teachers. Strengthening these skills is crucial for preparing future educators capable of designing and implementing effective integrated science learning strategies. Further research is recommended to explore instructional models and scaffolding techniques that can better support the development of these competencies across diverse scientific topic.